Reforming China's Public Finances. (International Monetary Fund, 1995)
The reform of fiscal relations between different levels of geovernment is crucial to the success of China's current structural transformation to a socialist market economy. The reform will profoundly affect macroeconomic stability, growth prospects , and the effectiveness of providing public services and interregional equity. In order to review international experience and to clearly identify the policy options for China in the short to medium term, a conference was held in Shanghai in October 1993. The papers in this volume, edited by Ehtisham Ahmad, Gao Qiang, and Vito Tanzi, include those presented at the conference and a few that supplement it.